THE IMPACT OF HARDINESS PERSONALITY AND PATIENCE ON HOMESICKNESS ACTIONS IN ANTAU STUDENTS - Hidayat, Ahmad; Arief, Yanwar; Widiantoro, Didik; Putri, Annisa (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2024)
Leaving their nest creates a distance between students and their hometown, which can lead to homesickness. Prolonged homesickness can create various adverse effects. It is speculated that a hardiness personality can mitigate the impacts of homesickness behavior for out-of-town students. Another factor that is assumed to reduce the impact of homesickness behavior is patience. In the context of Islamic teachings, patience (sabr) and hardiness, which closely aligns with the concept of istiqamah, are highly valued virtues. This study aimed to examine the influence of patience and hardiness personality on homesickness behavior for out-of-town students. The respondents in this study were 102 out-of-town students. Purposive sampling method was used to select the respondents by setting specific criteria. Data were collected using scales. This study analyzed the data using the Partial Least Squares (PLS) method with the help of the smartPLS 3.0 software. The conclusion of this study was based on the path coefficient values, which showed a negative influence of hardiness personality on homesickness behavior with a coefficient of -0.313 and a significant effect with a value of 0.011. The path coefficient values also showed a negative influence of patience on homesickness behavior with a coefficient of -0.318 and a significant effect with a value of 0.006. Therefore, it can be interpreted that both patience and hardiness personality have an influence on homesickness behavior for out-of-town students.